KEMAMPUAN GOOD CORPORATE GOVERNANCE DALAM MEMODERASI PENGARUH INTELLECTUAL CAPITAL DISCLOSURE DAN REPUTASI AUDITOR PADA NILAI PERUSAHAAN - Suparsa, I Made Joni; Ramantha, I Wayan; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
The purpose of this study was to obtain empirical evidence about the ability of good corporate governance in the moderating influence of intellectual capital disclosure and auditor reputation on the value of companies listed on the Indonesia Stock Exchange 2011-2014 period. Signalling Theory, Contingency Theory and Legitimacy Theory is a theory that underlies this study. The sampling method used was purposive sampling, and the sample size in the study was 56 companies. The analysis technique used is Moderated Regression Analysis (MRA). The results obtained indicate that good corporate governance is not able to moderate the influence of intellectual capital disclosure in the company's value. But good corporate governance reinforces the influence of auditor reputation on the value of the company.
Keywords: intellectual capital disclosure, auditor reputation, good corporate governance, the company' s value